Focal adhesion kinase (FAK1) regulates SHB phosphorylation and its binding with a range of signaling proteins - Dergai, O.V.; Yaruchik, A.M.; Rynditch, A.V. (Вiopolymers and Cell, 2016)
Aim. To investigate an effect of the Focal adhesion kinase 1 (FAK1) expression on the level of tyrosine phosphorylation of an adaptor protein SHB and to find functional consequences of this posttranslational modification. Methods. Recombinant DNA construction, protein expression and purification, human cell transfection, western blot. Results. The expression of FAK1 induces the massive tyrosine phosphorylation of SHB adaptor and enhances its interaction in vitro with SH2 domains of a range of the signaling proteins such as PI3K, ABL, CRK and PLCG1. Additionally we have found that Epstein-Barr virus protein LMP2A can partially mimic the FAK1-mediated effect strongly elevating the efficiency and SHB interaction with the mentioned above proteins. While the expression of individual proteins elevated SHB phosphorylation level, the co-expression of LMP2A and FAK1 did not display a synergetic effect. Conclusions. FAK1 as well as LMP2A induce the SHB tyrosine phosphorylation and enhance its interaction with a set of the signaling proteins.